Assessment of the Eating Disorders in Female Students of Shahid Sadoughi University of Medical Sciences, Yazd, Iran, 2011 - Azadeh Nadjarzadeh; Niloofar Vaziri; Ali Mohammad imanesh; Zahra Naderi; Hoorieh Daneshbodi; Farimah Shamsi; Mohammad Hassan Lotfi (Shahid Sadoughi University of Medical Sciences, 2012)
Introduction: Up to now, the number of epidemiological studies about eating disorders (ED) in Iran is still limited. This study determined the prevalence of eating disorders in female students of Shahid Sadoughi University of Medical Sciences. Materials & Methods: A randomly selected group of 400 female students studied at Shahid Sadoughi University of Medical Sciences had been assessed. After measuring height and weight, participants were invited to complete the Eating Attitude Questionnaire (EAT-26). Results: Questionnaire was completed by 366 students (91.5%). An average prevalence of anorexia (13.11%) was found for female students. Current dieting for losing weight was reported by 20% of participants. 11.5% of participants were thin and 88% of them were not satisfied with their own weight. Frequency of eating disorders was significantly higher among overweight/obese students (p<0.001). Conclusion: Eating disorders were present in over 13 percent of female university students. Preventive programs in order to decrease the progression of these disorders should be addressed.